2015
DOI: 10.1016/j.bjane.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiologist: the patient's perception

Abstract: Patients need to be informed about the current safety of anesthesia and the anesthesiologist's functions. The patient involvement will demystify some fears and reassure the confidence in the health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
2
17
1
3
Order By: Relevance
“…We found that 92.9% of the respondents knew that the anaesthesiologist provides anaesthesia as opposed to other studies where the percentage varied between 25.2% and 86% [3,[11][12][13][14][15][16]. This rather higher rate could be explained by a significant number of respondents with high degrees of education (65.2%), but also by a reduced concern of social desirability bias because some respondents were aware that an anaesthesiologist distributed the polls.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…We found that 92.9% of the respondents knew that the anaesthesiologist provides anaesthesia as opposed to other studies where the percentage varied between 25.2% and 86% [3,[11][12][13][14][15][16]. This rather higher rate could be explained by a significant number of respondents with high degrees of education (65.2%), but also by a reduced concern of social desirability bias because some respondents were aware that an anaesthesiologist distributed the polls.…”
Section: Discussioncontrasting
confidence: 77%
“…It differs from other studies in which the respondents were patients planned for elective surgery [3,6,[10][11][12][13][14][15][16][17]. We tried to obtain a more objective perspective of people's perception looking to a whole heterogeneous sample of the population, as this would give a better image of our reflection.…”
Section: Discussionmentioning
confidence: 99%
“…Düzenlenmiş olan başka anket çalışmalarında, anesteziyoloğun uzmanlaşmış bir doktor olduğu farkındalığı %58 ile %95 arasında değişenkenlik göster-mektedir (1,3,4) . Marulasiddappa ve ark.…”
Section: Discussionunclassified
“…Anesthesia has developed after the first anesthesia was administered by TG Morton in 1846, it has a supportive role in performing advanced surgeries (Ribeiro et al, 2015). Anesthesiology is one of medical Science branches (Sable et al, 2016), it has been grown in the recent pastyears (Cooper et al, 1995), by development of monitoring system, new anesthetic agents and techniques (Khara et al, 2013), however it is behind the light, the knowledge about this specialty and the exact role of anesthesiologists is limited between public (Cooper et al, 1995).After the great advances in anesthesia field (Lee et al, 2014), now anesthesiologists play a very important role in peri-operative, the operating room, intensive care, trauma centers,pain management and on the code team (Lee et al, 2014;Prasad et al, 2014; Kadriet al, 2014), however they don't receive the deserved attention andtheir due regards between public (Prasad et al, 2014), this limited awareness of public about the anesthesiologist exceeds anesthesiologist's role in the operating room (Ribeiro et al, 2015), reaching to anesthetist's roles outside the operation room (Garry, 2001).…”
mentioning
confidence: 99%
“…Anesthesiology is one of medical Science branches (Sable et al, 2016), it has been grown in the recent pastyears (Cooper et al, 1995), by development of monitoring system, new anesthetic agents and techniques (Khara et al, 2013), however it is behind the light, the knowledge about this specialty and the exact role of anesthesiologists is limited between public (Cooper et al, 1995).After the great advances in anesthesia field (Lee et al, 2014), now anesthesiologists play a very important role in peri-operative, the operating room, intensive care, trauma centers,pain management and on the code team (Lee et al, 2014;Prasad et al, 2014; Kadriet al, 2014), however they don't receive the deserved attention andtheir due regards between public (Prasad et al, 2014), this limited awareness of public about the anesthesiologist exceeds anesthesiologist's role in the operating room (Ribeiro et al, 2015), reaching to anesthetist's roles outside the operation room (Garry, 2001). This lack in public awareness about anesthetist's role is not new (Armitage, 1978).Many studies have reported a low public awareness about anesthesia and the role of anesthetists in both developing and developed countries (Swinhoe et al, 1994;Jathar et al, 2002).Patients think that the surgeon is responsible for tasks of anesthesia(Acosta-Martínez et al, 2016),44.5% think so, while only 22% of them know that anesthesiologistswere the providers of anesthesia ISSN: 2320-5407 Int.…”
mentioning
confidence: 99%